The Social Context of Adolescent Co-Use of Cigarillos and Marijuana Blunts. (21st March 2018) - Antognoli, Elizabeth; Koopman Gonzalez, Sarah; Trapl, Erika; Cavallo, David; Lim, Rock; Lavanty, Brittany; Flocke, Susan
ABSTRACT: Background : The use of cigarillos for smoking as a tobacco product and for making marijuana blunts is increasing among adolescents. Previous research has documented the co-use of these products, however little is known about the contextual features that generate and sustain this practice. Objective : This study aims for a deeper understanding of why and how co-use of cigarillos and marijuana blunts occurs. Methods : Between December 2015 and April 2016, we conducted in-depth interviews with 30 adolescents aged 14-18 who reported smoking ≥1 cigarillo per week. Semi-structured interviews were designed to capture participants' smoking products, practices, and preferences, as well as their beliefs and experiences about smoking. Interviews were audio-recorded and transcribed. Analysis was guided by a phenomenological approach designed to identify emergent themes. Results : All participants reported smoking cigarillos for use as a tobacco product, averaging 13 per week. Twenty-five (83%) also reported using cigarillos to smoke marijuana blunts. A preference for group smoking and product sharing, and the belief that cigarillos extend the high of marijuana were found to promote the co-use of these products. Cigarillos were also found to be used as a substitute for blunts when marijuana was unavailable or when its use was being restricted or monitored. Conclusions/Importance : This analysis of adolescent cigarillo and marijuana co-use demonstrates how marijuana use can initiate, increase, and reinforce tobacco use. These findings can be used to inform public health education campaigns and other programs and policies aimed at reducing cigarillo and marijuana use by youth.